Two Tomato Expansin Genes Show Divergent Expression and Localization in Embryos during Seed Development and Germination - Chen, Feng (American Society of Plant Physiologists, 2001)
Expansins are plant proteins that can induce extension of isolated cell walls and are proposed to mediate cell expansion. Three expansin genes were expressed in germinating tomato (Lycopersicon esculentum Mill.) seeds, one of which (LeEXP4) was expressed specifically in the endosperm cap tissue enclosing the radicle tip. The other two genes (LeEXP8 and LeEXP10) were expressed in the embryo and are further characterized here. LeEXP8 mRNA was not detected in developing or mature seeds but accumulated specifically in the radicle cortex during and after germination. In contrast, LeEXP10 mRNA was abundant at an early stage of seed development corresponding to the period of rapid embryo expansion; it then decreased during seed maturation and increased again during germination. When gibberellin-deficient (gib-1) mutant seeds were imbibed in water, LeEXP8 mRNA was not detected, but a low level of LeEXP10 mRNA was present. Expression of both genes increased when gib-1 seeds were imbibed in gibberellin. Abscisic acid did not prevent the initial expression of LeEXP8 and LeEXP10, but mRNA abundance of both genes subsequently decreased during extended incubation. The initial increase in LeEXP8, but not LeEXP10, mRNA accumulation was blocked by low water potential, but LeEXP10 mRNA amounts fell after longer incubation. When seeds were transferred from abscisic acid or low water potential solutions to water, abundance of both LeEXP8 and LeEXP10 mRNAs increased in association with germination. The tissue localization and expression patterns of both LeEXP8 and LeEXP10 suggest developmentally specific roles during embryo and seedling growth.